Effects of cellulase-containing enzymes on auxin heterotrophic and autotrophic tobbaco tissue cultures - Szabó, Margit (Acta Biologica Szegediensis, 2005)
During the digestion of cell wall by cellulases, rapid cell death of auxin heterotrophic and autotrophic tobacco tissue cells has been observed. Under these conditions a considerable amount of H2O2 is secreted into the medium. It is suggested that the rapid cell death induced by cellullysin is partly a result of the hypersensitive defense reaction against cellulysin from the parasitic fungus Trichoderma viride. The absolute amount of secreted H2O2 is higher in the case of heterotrophic cells, but the quantity of H2O2 is greater in the medium of auxin autotrophic cultures as compared with control cells without cellulysin. These cells emit more cellulase-dependent ethylene than the auxin heterotrophic line. Cellulysin induces an increasing intracellular H2O2 level only in the cells of auxin heterotrophic tissues. There are differences between the two cell lines in the change in cytosolic Ca2+ concentration in response to exogenous H2O2.